Pengaruh Kemiringan Pipa pada Hidroponik Sistem NFT terhadap Pertumbuhan dan Produksi Pakcoy Putih (Brassica rapa L.) - Faiz Fadhlillah; Nurlaila Fatmawati (Politeknik Negeri Lampung, 2026)
The purpose of this study was to determine the optimal gully slope and evaluate the effect of different gully slope levels in a Nutrient Film Technique (NFT) hydroponic system on the growth and yield of white pakcoy (Brassica rapa L.). The study was conducted from February to March 2026 in Bantarwaru Village, Madukara District, Banjarnegara Regency. This study employed a single-factor Completely Randomized Design (CRD) with six replications. The treatments consisted of four gully slope levels: 1% (K1), 3% (K2), 5% (K3), and 7% (K4). The results showed that gully slope had a significant effect on plant height, stem diameter, root length, root weight, fresh weight, and dry weight, but had no significant effect on the number of leaves. The K3 treatment (5% slope) produced the best results for almost all growth and yield parameters, including plant height (26.067 cm), stem diameter (6.50 mm), root length (19.83 cm), root weight (14.57 g), fresh weight (173.00 g), and dry weight (40.26 g).